A primary source guide to Norway - Rose, Elizabeth, 1970- (New York : PowerKids Press, 2004)
Contains general information about the landscape, economy, original inhabitants, culture, and neighbors of Norway, and includes vocabulary words.
Includes index.
4.7
3-6
Keywords: Norway -- Juvenile literature; Norway; Norway